Epigenetic Silencing of Human Immunodeficiency Virus (HIV) Transcription by Formation of Restrictive Chromatin Structures at the Viral Long Terminal Repeat Drives the Progressive Entry of HIV into Latency - Pearson, Richard; Kyeung Kim, Young; Hokello, Joseph; Lassen, Kara; Friedman, Julia; Tyagi, Mudit; Karn, Jonathan (Journal of virology, 2008)
The molecular mechanisms utilized by human immunodeficiency virus (HIV) to enter latency are poorly understood. Following the infection of Jurkat T cells with lentiviral vectors that express Tat in cis, gene expression is progressively silenced. Silencing is greatly enhanced when the lentiviral vectors carry an attenuated Tat gene with the H13L mutation. Individual clones of lentivirus-infected cells showed a wide range of shutdown rates, with the majority showing a 50% silencing frequency between 30 to 80 days. The silenced clones characteristically contained a small fraction (0 to 15%) of activated cells that continued to express d2EGFP. When d2EGFP and d2EGFP cell populations were isolated from the shutdown clones, they quickly reverted to the original distribution of inactive and active cells, suggesting that the d2EGFP cells arise from stochastic fluctuations in gene expression. The detailed analysis of transcription initiation and elongation using chromatin immunoprecipitation (ChIP) assays confirms that Tat levels are restricted in the latently infected cells but gradually rise during proviral reactivation. ChIP assays using clones of latently infected cells demonstrate that the latent proviruses carry high levels of deacetylated histones and trimethylated histones. In contrast, the cellular genes I B and GAPDH had high levels of acetylated histones and no trimethylated histones. The levels of trimethylated histone H3 and HP1- associated with HIV proviruses fell rapidly after tumor necrosis factor alpha activation. The progressive shutdown of HIV transcription following infection suggests that epigenetic mechanisms targeting chromatin structures selectively restrict HIV transcription initiation. This decreases Tat production below the levels that are required to sustain HIV gene expression.
Keywords: Immunodeficiency; Virus (HIV); Chromatin Structures